Learning Tenses Using “Tepuk Keledai Cerdik” Technique for First Semester Students of English Education Program - Al Hikmah (CLLiENT (Culture, Literature, Linguistics, and English Teaching), 2020)
Tenses materials are basic grammar lessons that make students better at understanding grammar learning at the next level. The learning situation in this monotonous pandemic period is, of course, very detrimental for students if lecturers do not try to create innovations and learning creations. "Tepuk Keledai Cerdik" is a language teaching technique, especially with regard to grammar which is closely related to tenses. These two methods, which are combined into one name, have brought significant results to the students' ability to understand tenses in English subjects. This research is a qualitative descriptive study. The method used in data collection is the direct method. The data collected from the results of the use of "Tepuk Keledai Cerdik" in learning tenses must be valid and reliable lingual data, because these two conditions are the main factors for proper analysis. "Tepuk Keledai Cerdik" has brought significant results to the students' ability to understand questions related to grammar. The results above indicate an increase in students' ability to speak English in writing by 45.78%. Tepuk Keledai Cerdik technique has been practiced by the author since 2018 in the basic communicative grammar course in the English Education study program. And this technique has brought significant results that are closely related to motivation, interest, the level of active participation of students in learning English and students' skills in solving problems in a logical and practical way. Keywords: Learning tenses; Tehnik Tepuk Keledai Cerdik